MANAGEMENT ON CORAL REEF ECOSYSTEM IN THE SIANTAN TENGAH DISTRICT, ANAMBAS ISLANDS - Rifki Aldi Ramadhani; Ario Damar; Hawis Madduppa (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Coral reef ecosystem management in Siantan Tengah District, Anambas Islands need to be improved to obtain the optimal results. Currently, the coral reef ecosystem management is conducted sectorally, therefore, it can cause a damage on coral reef ecosystem. The purposes of this study were to analyze sustainability status of coral reefs managements in the District Central Siantan and to formulate the sustainability of coral reef ecosystem management. Multi Dimensional Scaling (MDS) with Rap-Insus COREMAG approach was used to analyze the sustainability status of coral reef management. The results showed that the sustainability status of coral reef management in Siantan Tengah District was sustainable with multidimensional index of 51.457. Dimensions that need to be improved to achieve the optimal management of coral reef ecosystems in a sustainable manner is social dimension to the value of sustainability by 42.324 and institutional dimensions of 49.85 which is classed as less sustainable. This results of this research are expected to be able to facilitate the stakeholders to arrange the sustainability of coral reef ecosystem management in the Siantan Tengah District. Keywords: coral reef management, sustainability analysis, Siantan Tengah District, Anambas Island, Multi Dimensional Scaling (MDS)